IMPLEMENTASI NILAI-NILAI KARAKTER DALAM PEMBELAJARAN IPA YANG TERINTEGRASI DI SEKOLAH DASAR - Ratna, Muttia; Lara S, Sylvia; Ayurachmawati, Puji (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
Presentation of character education through learning in school becomes one of the main points in shaping the personality of learners. The updating of the curriculum that leads to the 2013 curriculum continues to be perfected by adapting the development of the era and the present era. The effort is done because so massive flow of information and technology that arise millennial generation that forget the application of character values. Instead of manifesting the values of characters in life, millennials now do not even have the moral knowledge that is qualified and good as a stock to plunge in the life of society. For this purpose, the purpose of this paper is to know the implementation of character values into the learning especially on learning science (Natural Science) integrated in elementary school. IPA is a subject that requires learners to have a scientific attitude that is meticulous attitude, curiosity, responsibility, and other attitudes that are in line with the values of character. The materials in science learning especially in high class are able to train learners to embody the values of character in everyday life.